(untitled) (American International Journal of Economics and Finance Research, 2021)
The importance of Corporate Social Responsibility has been acknowledged greatly as an objective of business sustainability. Whereas the measurement of CSR is always a source of argument among researchers. There are different approaches identified and used by researchers to measure CSR. The main objective of this study is to measure CSR disclosure by constructing an index based on content analysis. The study used the data of non-financial listed companies’ annual reports to construct an index for the period 2016, 2017, 2018, and 2019. Thus, 291 firm-year observations are used in this study to construct and measure the CSR disclosure index. 40 elements are used to measure CSR disclosure based on five sub-themes. The result of the study reveals that as CSR disclosure requirement is mandatory in Oman according to the new corporate governance system, thus the listed companies are trying to cope and developing CSR charters. The evidence indicates that some companies have high CSR disclosure while few companies are still struggling with developing CSR charter and disclosing their activities. However, CSR disclosure improves significantly from 2016 to 2019, which shows a strict implementation of the code of corporate governance.